2018
DOI: 10.1016/j.jpor.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Color stability of glass-fiber-reinforced polypropylene for non-metal clasp dentures

Abstract: The results indicate that the GFRTPs showed clinically acceptable color stability and might be satisfactory for clinical use. Therefore, GFRTPs are expected to become attractive materials for esthetic dentures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…To determine the relationship between the amount of color alteration recorded on a spectrophotometer to the clinical environment, data was converted to the National Bureau of Standards (NBS) system units as follows: (See [ 20 ].) The defined critical remarks of color change according to the quantified NBS units are given in Table 2 [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…To determine the relationship between the amount of color alteration recorded on a spectrophotometer to the clinical environment, data was converted to the National Bureau of Standards (NBS) system units as follows: (See [ 20 ].) The defined critical remarks of color change according to the quantified NBS units are given in Table 2 [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…GFRTPs composed of E-glass fibers, a polypropylene matrix, and a small amount of coloring pigment were produced by injection-molding pellets (Plastron, PP-GF50-02, Daicel Polymer, Tokyo, Japan) consisting of polypropylene reinforced with E-glass fibers of diameter 17 µm and length 10 mm, and 2 mass% of pigment (Aesthetic Intensive-Colors: Purpur Red, Candulor, Glattpark, Switzerland); this process is described in detail elsewhere 2,5) . According to a previous study on the optimum fiber contents of GFRTPs, GFRTPs were prepared with fiber contents of 0 mass% (GF0), 10 mass% (GF10), and 20 mass% (GF20).…”
Section: Preparation Of Gfrtpsmentioning
confidence: 99%
“…A novel NMCD made from the GFRTPs designed in a previous study is esthetically pleasing and has sufficient rigidity, and its properties can be controlled based on the fiber loading and pigmentation 4) . Furthermore, the GFRTPs have clinically acceptable color stability and might be satisfactory for clinical use 5) .…”
Section: Introductionmentioning
confidence: 99%
“…When specimens stored in distilled water at 7 days were compared with baseline data, the finding showed that there were slight changes in colour values between the groups containing zirconia and the control group (without ZrO 2 ) ( Table 4). As the concentration of ZrO 2 increased, the colour change increased, however, these changes were clinically acceptable according to NBS [20,21]. Therefore, the combined effect of the cleaning solutions and concentration of ZrO 2 nanoparticles could be accounted for the colour change in the nanocomposite specimens.…”
Section: Discussionmentioning
confidence: 99%